Hydraulic performance assessment of various submerged pile designs around an emerged dike - Iqbal, Sohail; Tanaka, Norio (Water Science and Engineering, 2024)
This study aimed to devise strategies for alleviating the detrimental impacts of floods in the vicinity of a dike. Experiments were conducted in an open rectangular channel to investigate the flow dynamics under varying dike conditions. To address concerns related to intense whirls and concentrated flow around the dike head, comparative analysis was performed in terms of flow structures and energy reduction around I-shaped and T-shaped dikes with two ratios of wing length (lw) to dike length (ld) (lw/ld = 1.41 and 2.43). The T-shaped dike wings were equipped with diverse designs: angled footing, delta vane, and streamlined tapered, resulting in elevated backwater in front of the dike, reduced velocity, and enhanced energy reduction. The findings indicated that elongating the wing reciprocally affected the depth-averaged velocity (at the dike head and near the adjacent dike bank), concurrently impacting flow deflection, backwater rise, and energy reduction rate. The T-shaped dike, specifically with an angled footing (lw/ld = 2.43), yielded optimal outcomes. These included significant reductions in maximum energy (46%), tip velocity (98%), and dike adjacent bank velocity (90%), as well as significant flow deflection towards the mainstream, outperforming the I-shaped impermeable dike. The proposed solutions exhibit efficacy in mitigating rapid deterioration during floods, securing both the dike head and the neighboring bank to avert failures in high-energy flow.